PEMANFAATAN PLATFORM DIGITAL DALAM PEMBELAJARAN TINGKAT SMA - yafita mu'ti (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
As a result of the Covid-19 pandemic, technology plays an important role in the world of education in Indonesia. Currently, when Covid-19 is over, technology has become an integral part of the student learning process at school and home. One of the roles of technology is to develop digital platforms, especially in education which is very beneficial for students, such as Teacher's Room, Learning House, Google Suite for Education, Quipper, and Zenius. This research aims to find out the digital platforms used by students at the high school level. Digital platforms have provided features that students and teachers can use as learning resources. The method used in this research is descriptive quantitative (observational) using a cross-sectional design. The subjects of this study were students of class XI IPS SMA N 1 Geger. The results showed that 37.14% used the Ruang Guru platform, 12.38% of students used the Rumah Belajar platform, 5.71% of students used Google Suite for Education, 23.81% of students used Qipper, and 20.95% of students used Zenius.